2014
DOI: 10.1016/j.celrep.2014.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Cortical Interneurons in Primates: The Role of the Dorsal Proliferative Niche

Abstract: SummaryEvolutionary elaboration of tissues starts with changes in the genome and location of the stem cells. For example, GABAergic interneurons of the mammalian neocortex are generated in the ventral telencephalon and migrate tangentially to the neocortex, in contrast to the projection neurons originating in the ventricular/subventricular zone (VZ/SVZ) of the dorsal telencephalon. In human and nonhuman primates, evidence suggests that an additional subset of neocortical GABAergic interneurons is generated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 72 publications
4
58
0
Order By: Relevance
“…These results suggest that the majority of neuronal subtypes in adult zebrafish telencephalon might derive from dRGCs and NBs might derive from mRGCs (Figure 3K). This prediction is supported by previous documentation of cortical neurons deriving from dorsal region of the vertebrate telencephalon (Cai et al, 2013; Radonjic et al, 2014) and a large portion of the proliferating cells in the zebrafish pallium are found in medial region (Adolf et al, 2006; Grandel et al, 2006; Kaslin et al, 2008; Kizil et al, 2012b; Than-Trong et al, 2018; Zupanc, 2008). Interestingly, we found that endothelial cells share 60% TF code similarity with dRGC populations (Figure 3J), suggesting that endothelial cells might be derived from dRGCs.…”
Section: Resultssupporting
confidence: 81%
“…These results suggest that the majority of neuronal subtypes in adult zebrafish telencephalon might derive from dRGCs and NBs might derive from mRGCs (Figure 3K). This prediction is supported by previous documentation of cortical neurons deriving from dorsal region of the vertebrate telencephalon (Cai et al, 2013; Radonjic et al, 2014) and a large portion of the proliferating cells in the zebrafish pallium are found in medial region (Adolf et al, 2006; Grandel et al, 2006; Kaslin et al, 2008; Kizil et al, 2012b; Than-Trong et al, 2018; Zupanc, 2008). Interestingly, we found that endothelial cells share 60% TF code similarity with dRGC populations (Figure 3J), suggesting that endothelial cells might be derived from dRGCs.…”
Section: Resultssupporting
confidence: 81%
“…For example, interneurons expressing tyrosine hydroxylase appear to be particularly abundant in deep layers of human neocortex relative to other mammalian species (Defelipe 2011). Variation in GABAergic neuron subtype proportions between human and mouse neocortex has also been attributed to species' differences in the neuroanatomical origins of these cells (Letinic et al 2002;Jakovcevski et al 2011;Yu and Zecevic 2011;Radonjic et al 2014a), although this interpretation is not universally accepted (Hansen et al 2013;Ma et al 2013). Our finding of molecular differences in SCGN activity between humans and mice provides further support for efforts to clarify species' differences among subpopulations of GABAergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to rodents and other commonly studied mammals, human neocortical excitatory glutamatergic projection neurons (also known as pyramidal neurons) are generated from progenitor cells of the dorsal pallium and migrate radially into the CP (Fietz et al, 2010; Hansen et al, 2010). In contrast, human GABAergic interneurons are largely generated ventrally from the ganglionic eminences in the basal ganglia primordia and migrate tangentially into the CP (Fertuzinhos et al, 2009; Hansen et al, 2013; Hansen et al, 2010; Ma et al, 2013; Radonjic et al, 2014). Unlike in the rodent, most stem cells in the human ganglionic eminences do not appear to be located in the epithelium, but rather comprise a more distributed population suggestive of a mechanism for expansion of the interneuron progenitor pool (Hansen et al, 2013).…”
Section: A Brief Overview Of Human Cns Developmentmentioning
confidence: 99%
“…For instance, many of the genes previously implicated in the generation and specification of distinct subtypes of cortical projection neurons (Leone et al, 2008; Molyneaux et al, 2007; Shibata et al, 2015) and interneurons (Southwell et al, 2014) have well conserved expression gradients and domains among neural stem/progenitor cells in the VZ/SVZ or neurons in the SP and CP (Bayatti et al, 2008; Hansen et al, 2013; Hevner, 2007; Kwan et al, 2008; Ma et al, 2013; Radonjic et al, 2014), indicating that human neocortical patterning employs many of the same principles observed across mammalian species. This suggests a degree of homology.…”
Section: The Transcriptional Landscape Of the Developing Human Cnsmentioning
confidence: 99%